Large-scale analyses of angiosperm Flowering Locus T genes reveal duplication and functional divergence in monocots - Liu, Hongling; Liu, Xing; Chang, Xiaojun; Chen, Fei; Lin, Zhenguo; Zhang, Liangsheng (Frontiers in Plant Science, 2023)
FLOWERING LOCUS T (FT) are well-known key genes for initiating flowering in plants. Delineating the evolutionary history and functional diversity of FT genes is important for understanding the diversification of flowering time and how plants adapting the changing surroundings. We performed a comprehensive phylogenetic analysis of FT genes in 47 sequenced flowering plants and 1,000 transcriptomes database (1KP) with a focus on monocots, especially cereals. We revealed the evolutionary history of FT genes. The FT genes in monocots can be divided into three clades (I, II, and III), while is monophyletic group in basal angiosperms, magnoliids and eudicots. Multiple rounds of whole genome duplications (WGD) events followed by gene retention contributed to expansion and variation of FT genes in cereals. Positively selected sites were identified in the clade II and III genes and some sites located in vital domain regions are known to changing functions when mutated, thus the clade I is more conserved than clade II and III. Genes in clade I displayed higher expression levels in studied organs and tissues than the clade II and III genes. The co-expression modules showed some of FT genes might have experienced neofunctionalization and subfunctionalization, such as the acquisition of environmental resistance. Overall, FT genes in monocots might form three clades by the ancient gene duplication, and each clade was subsequently subjected to different selection pressures and amino acid substitutions, which eventually led to different expression patterns and functional diversification. Our study provides a global picture of FT genes’ evolution in monocots, paving a road for investigating FT genes’ function in future.